Phylogeography and Population Genetics of Vicugna vicugna: Evolution in the Arid Andean High Plateau - González, Benito A.; Vásquez, Juan P.; Gómez-Uchida, Daniel; Cortés, Jorge; Rivera, Romina; Aravena, Nicolas; Chero, Ana M.; Agapito, Ana M.; Varas, Valeria; Wheleer, Jane C.; Orozco-terWengel, Pablo; Marín, Juan Carlos (Frontiers in Genetics, 2019)
The vicuña (Vicugna vicugna) is the most representative wild ungulate of the high Andes of South America with two recognized morphological subspecies, V. v. mensalis in the north and V. v. vicugna in the south of its distribution. Current vicuña population size (460,000–520,000 animals) is the result of population recovery programs established in response to 500 years of overexploitation. Despite the vicuña’s ecosystemic, economic and social importance, studies about their genetic variation and history are limited and geographically restricted. Here, we present a comprehensive assessment of the genetic diversity of vicuña based on samples collected throughout its distribution range corresponding to eleven localities in Peru and five in Chile representing V. v. mensalis, plus four localities each in Argentina and Chile representing V. v. vicugna. Analysis of mitochondrial DNA and microsatellite markers show contrasting results regarding differentiation between the two vicuña types with mitochondrial haplotypes supporting subspecies differentiation, albeit with only a few mutational steps separating the two subspecies. In contrast, microsatellite markers show that vicuña genetic variation is best explained as an isolation by distance pattern where populations on opposite ends of the distribution present different allelic compositions, but the intermediate populations present a variety of alleles shared by both extreme forms. Demographic characterization of the species evidenced a simultaneous and strong reduction in the effective population size in all localities supporting the existence of a unique, large ancestral population (effective size ∼50,000 individuals) as recently as the mid-Holocene. Furthermore, the genetic variation observed across all localities is better explained by a model of gene flow interconnecting them rather than only by genetic drift. Consequently, we propose space “continuous” Management Units for vicuña as populations exhibit differentiation by distance and spatial autocorrelation linked to sex biased dispersal instead of population fragmentation or geographical barriers across the distribution.